2017
DOI: 10.1017/s0021932017000463
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Its Relationship With Nutritional Status Among Adolescents and Adults in Rural India

Abstract: Summary. Dietary diversity is associated with household or individual food availability and intake of nutrients from different food groups and is an important component of nutritional outcome. This study examined the Nutrient Adequacy Ratio (NAR) and the Mean Adequacy Ratio (MAR) of three dietary diversity indices and their relationship with the nutritional status of adolescents and adults in rural regions of two states in India, Wardha district in Maharashtra and Koraput district in Odisha, in 2014. Individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 26 publications
5
68
2
2
Order By: Relevance
“…Dietary diversity over a three day period (as in this present study) will undoubtedly be higher than that observed during one day, which might be another reason for the higher DDS in our study. Worldwide there is also a large variety of DDS and FVS values reported among studies, which again appears to be due to differences in how the parameters used have been defined and calculated [ 8 , 9 , 19 ]. These differences include variations in definitions of the food groups (e.g., the number and make up of food groups used, or the use of food codes or even food ingredients in some studies), applying thresholds of intake for each food group, and different methods for extracting diversity and variety data, such as using one 24-h recall period versus three or seven 24-h recall periods, or even food frequency questionnaires (FFQ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary diversity over a three day period (as in this present study) will undoubtedly be higher than that observed during one day, which might be another reason for the higher DDS in our study. Worldwide there is also a large variety of DDS and FVS values reported among studies, which again appears to be due to differences in how the parameters used have been defined and calculated [ 8 , 9 , 19 ]. These differences include variations in definitions of the food groups (e.g., the number and make up of food groups used, or the use of food codes or even food ingredients in some studies), applying thresholds of intake for each food group, and different methods for extracting diversity and variety data, such as using one 24-h recall period versus three or seven 24-h recall periods, or even food frequency questionnaires (FFQ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Asia have reported that dietary diversity can be a valuable indicator to predict macronutrient or micronutrient adequacy for children [ 7 , 8 , 9 ]. The latest study in India (among adolescents) found that the nutrient adequacy ratio (NAR) of most micronutrients studied increased with the dietary diversity score (DDS), allowing them to conclude that nutrient adequacy was positively associated with high dietary diversity [ 8 ]. In a study conducted in the Philippines, DDS was found to be both significantly correlated to the mean probability of adequate nutrient intake (MPA) and to the intake of most micronutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Mean adequacy ratio (MAR) was calculated as an overall measure of nutrient adequacy of the different meal and snack patterns . Recommended Daily Allowance and Adequacy Intake (when the formers were not available) cut‐offs, as proposed by the ΙΟΜ, were used to compute for the nutrient adequacy ratio (NAR).…”
Section: Methodsmentioning
confidence: 99%
“…Hal tersebut dapat berpengaruh terhadap metabolisme tubuh dan akhinya berdampak pada terjadinya status gizi kurang pada individu. 31,32 Namun, disisi lain, penelitian yang dilakukan di Afrika Utara menunjukkan bahwa tidak ada korelasi yang signifikan antara usia ibu dan kejadian beban gizi ganda pada keluarga. 33 Hasil analisis menunjukkan bahwa jumlah anak juga berhubungan dengan terjadinya beban gizi ganda pada keluarga.…”
Section: Tabel 2 Prevalensi Dan Persebaran Status Gizi Keluarga Menuunclassified